2022
DOI: 10.1155/2022/4159996
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Atropine Eye Drops Combined with VR-Based Binocular Visual Function Balance Training for Prevention and Control of Juvenile Myopia

Abstract: Purpose. This study mainly analyzes the efficacy of 0.01% atropine eye drops (low-dose atropine (LDA)) combined with virtual reality (VR)-based binocular visual function (BVF) balance training in the prevention and control of juvenile myopia. Methods. One hundred and thirty-six juvenile myopia patients admitted between November 2018 to November 2021 were selected, including 76 cases (research group) receiving LDA + VR-based BVF balance training and 60 cases (control group) treated by LDA intervention alone. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…After screening by title and abstract, 171 articles were selected for full‐text view. Finally, 31 studies were identified that fulfilled the eligibility criteria 12–42 . The study flow was depicted according to the PRISMA guidelines in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After screening by title and abstract, 171 articles were selected for full‐text view. Finally, 31 studies were identified that fulfilled the eligibility criteria 12–42 . The study flow was depicted according to the PRISMA guidelines in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of this study is to examine myopia prevention and control methods from the standpoint of visual training. VR-based binocular visual function (BVF) balance training ( 27 ), is a form of binocular vision training that patients can receive by wearing VR visual training glasses ( Figure 3 ). In order to avoid myopia and reduce visual fatigue, it helps patients thoroughly exercise their ciliary muscles through visual training, scenes, movies, games, experience halls, and other locations ( 28 ).…”
Section: Vr Exercises For Prevention and Control Of Human Ocular Dise...mentioning
confidence: 99%
“…Finally, 9 studies that met all inclusion criteria were included in this meta-analysis. [14][15][16][18][19][20][21][22][23] Figure 1 showed the selection process of eligible articles. A total of 191 children in OKA group and 196 children in OK group were assessed.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…[13] There are a small number of studies have shown that the combination of orthokeratology and atropine can enhance the effect of myopia control. [14][15][16] However, due to individual differences, research groups, drug concentrations, and research design differences, the safety and effectiveness of the combined treatment still need to be verified. Therefore, the present meta-analysis aimed at determining the effect of 0.01% atropine on ocular axial elongation for myopia children.…”
Section: Introductionmentioning
confidence: 99%